Navigating nourishment: Unveiling disparities between rural and urban food environment - A case study in Kenya - Odongo, Nicanor; Induli, Irene; Akingbemisilu, Tosin; Jordan, Irmgard; Frei, Michael; Teuber, Ramona; Termote, Celine (2024)
• Across Low- and Middle-Income Countries (LMIC), changing food environments have led to changes in dietary patterns from traditional diets, high in nutrients, to highly processed foods, which are nutrient poor among both urban and rural populations (Downs et al., 2022). • There is lack of useful food environment data to inform policies in Africa (Turner et al., 2020). • Study aim: provide context-specific data for both rural and urban food environments to inform policy interventions aimed at supporting healthy diets.